Visokotemperaturna oksidacija grafita - Javorič, Saša (Vakuumist, 1996)
A major problem of C/C composites is their application in oxidative environments. Due to the of carbon burn off from fibers and matrix during oxidation, the cracking and erosion of fiber and matrix structure appear. Withprotective layer on the surface, it is possible to reduce the burn off of the carbon. Durin oxidation of oxide layer forms and prevents diffusion of oxygen into the composite. Results show that protective layers of SiC and B4C offer efficient protection against oxidation in the temperature interval between 600 and 1000 C.
Keywords: grafit; ogljik; oksidacija